DNase γ Is the Effector Endonuclease for Internucleosomal DNA Fragmentation in Necrosis - Mizuta, Ryushin (Public Library of Science, 2013)
Apoptosis and necrosis, two major forms of cell death, can be distinguished morphologically and biochemically. Internucleosomal DNA fragmentation (INDF) is a biochemical hallmark of apoptosis, and caspase-activated DNase (CAD), also known as DNA fragmentation factor 40 kDa (DFF40), is one of the major effector endonucleases. DNase γ, a Mg(2+)/Ca(2+)-dependent endonuclease, is also known to generate INDF but its role among other apoptosis-associated endonucleases in cell death is unclear. Here we show that (i) INDF occurs even during necrosis in cell lines, primary cells, and in tissues of mice in vivo, and (ii) DNase γ, but not CAD, is the effector endonuclease for INDF in cells undergoing necrosis. These results document a previously unappreciated role for INDF in necrosis and define its molecular basis.